Influence of medium viscosity and intracellular environment on the magnetization of superparamagnetic nanoparticles in silk fibroin solutions and 3T3 mouse fibroblast cell cultures. (17th July 2018) - Urbano-Bojorge, Ana Lorena; Casanova-Carvajal, Oscar; Félix-González, Nazario; Fernández, Laura; Madurga, Rodrigo; Sánchez-Cabezas, Santiago; Aznar, Elena; Ramos, Milagros; Serrano-Olmedo, José Javier
Abstract: Biomedical applications based on the magnetic properties of superparamagnetic iron oxide nanoparticles (SPIONs) may be altered by the mechanical attachment or cellular uptake of these nanoparticles. When nanoparticles interact with living cells, they are captured and internalized into intracellular compartments. Consequently, the magnetic behavior of the nanoparticles is modified. In this paper, we investigated the change in the magnetic response of 14 nm magnetic nanoparticles (Fe3 O4 ) in different solutions, both as a stable liquid suspension (one of them mimicking the cellular cytoplasm) and when associated with cells. The field-dependent magnetization curves from inert fluids and cell cultures were determined by using an alternating gradient magnetometer, MicroMagTM 2900. The equipment was adapted to measure liquid samples because it was originally designed only for solids. In order to achieve this goal, custom sample holders were manufactured. Likewise, the nuclear magnetic relaxation dispersion profiles for the inert fluid were also measured by fast field cycling nuclear magnetic relaxation relaxometry. The results show that SPION magnetization in inert fluids was affected by the carrier liquid viscosity and the concentration. In cell cultures, the mechanical attachment or confinement of the SPIONs inside the cells accounted for the change in the dynamic magnetic behavior of the nanoparticles. Nevertheless, the magnetization value in the cell cultures was slightly lower than that of the fluid simulating the viscosity of cytoplasm, suggesting that magnetization loss was not only due to medium viscosity but also to a reduction in the mechanical degrees of freedom of SPIONs rotation and translation inside cells. The findings presented here provide information on the loss of magnetic properties when nanoparticles are suspended in viscous fluids or internalized in cells. This information could be exploited to improve biomedical applications based on magnetic properties such as magnetic hyperthermia, contrast agents and drug delivery.